The atypical cadherin Dachsous1 localizes to the base of the ciliary apparatus in airway epithelia - Dau, Cécile Ngoc Dung; Kriz, Wilhelm (Biochemical and biophysical research communications, 2016)
Mucociliary clearance requires the distinct orientation and coordinated movement of airway cilia, which is established through planar cell polarity signaling (PCP). The atypical cadherin Dachsous1 (Dchs1) is a transmembrane protein that regulates PCP in D. melanogaster. However, little is known about Dchs1 expression and its potential role in PCP in mammalian adult tissues. Here, we show that Dchs1 is ubiquitously expressed in mouse embryos, but exhibits a highly restricted expression to lung tissues in the adult stage. Strikingly, human Dchs1 localized exclusively to the base of the ciliary apparatus in cultured human respiratory epithelial cells with differentiated motile 9 + 2 cilia. This localization could be functionally important as we observed aberrant DCHS1 mRNA expression in human non-small cell lung cancer tissue. In sum, we establish Dchs1 as a component of the membrane domain surrounding the ciliary base. This suggests a specific role of Dchs1 in PCP-dependent organization of ciliary function and a possible role in lung disease.